Azospirillum inoculation of 'Marandu' palisade grass seeds: Effects on forage production and nutritional status - Heinrichs, Reges [UNESP]; Meirelles, Guilherme Constantino [UNESP]; De Melo Santos, Luiz Felipe [UNESP]; Da Silva Lira, Maikon Vinicius; De Marcos Lapaz, Allan [UNESP]; Nogueira, Marco Antonio; Dos Santos Batista Bonini, Carolina [UNESP]; Filho, [UNESP]; Moreira, Adônis (Universidade Estadual de Londrina, 2020)
Plant-growth-promoting bacteria can be used for sustainable forage grass production while increasing nutrition and biomass. Most of the soils under pasture in the tropics have a degradation level that impairs the forage yield potential, especially because of mismanagement and lack of fertilization. The objective of this work was to evaluate the seed inoculation effects of Azospirillum brasilense on the shoot and root dry mass production and nutritional status of Urochloa brizantha cv. 'Marandu' under field conditions for two years in a fertility soil. The experimental design was a randomized block design with four replications, arranged in a 2 × 3 factorial scheme, comprised of two doses of A. brasilense (0 and 200 mL ha-1) in combination with three doses of N (0, 25 and 50 kg ha-1). Seed inoculation increased shoot dry mass by 13% in the first year and by 6% in the second year, whereas N application increased dry mass by 27% and 35% in the first and second year, respectively. The concentration of nutrients in the shoots did not change due to the inoculation, but N fertilization affected P, Mg, Fe, Mn, and Zn in the first year and N, P and Cu in the second year. Root dry mass increased 36% with fertilization of 25 kg N ha-1 plus inoculation in relation to the other treatments in the first year. In the second year, the inoculation of A. brasilense increased by 17%. Therefore, seed inoculation of Urochloa brizantha cv. 'Marandu' with Azospirillum brasilense increased root and shoot dry mass production in some cuts without influencing tiller numbers. Nitrogen fertilization altered N, Mg, P, Fe, Mn, Zn, and Cu concentrations in shoot dry mass.
Keywords: Diazotrophic bacteria; Growth promoting; Nitrogen; Pasture; Urochloa brizantha